A STUDY OF ANDROGEN AND ESTROGEN RECEPTORS α, β IN SKIN TAGS - El Safoury, Omar (Medknow Publications, 2010)
BACKGROUND: In women, the age of 50 is suggested to be the turning point of life at which the development of skin tags comes to a stop. A major event that occurs around this period of life is menopause/andropause. After menopause, estrogen receptors amounts decrease significantly. As skin is considered as the largest nonreproductive target on which estrogens and androgens act, we assume a possible relationship between the pathogenesis of skin tags and sex steroid balance. Another phenomenon is the association of skin tags in obese patients, which may also be explained by the interplay of sex steroids and their receptors in skin tags. AIMS: Here we see that in obese patients, hyperandrogenism occurs as a result of hyperinsulinemia as well as peripheral conversion of estrogens into androgens in the excessive adipose tissue. To examine the possible role of androgen and estrogen receptors in etiopathogenesis of skin tags. MATERIALS AND METHODS: To examine these hypotheses, we measured the level of androgen and estrogen receptors (both α and β) in skin tags compared to control. We also correlated the level of receptors to body mass index, and compared those levels in patients with acanthosis nigricans compared to normal. RESULTS: The level of estrogen receptors (both α and β) was significantly higher in skin tags than in controls with a P value of 0.004 and 0.001, respectively. The same upsurge was found for androgen receptors in skin tags relative to control with a P value of 0.001. No statistically significant difference in receptor level was found either among patients with acanthosis nigricans and those without, or in correlation to body mass index (our participants were overweight non diabetic). CONCLUSION: These results suggest the possible role of androgen and estrogen receptors in etiogenesis of skin tags, and propose that the neck is an androgen dependent area just similar to the axillae and the groins, though hairless.